Spatial planning of land use in the scientific research system of the national academy of agrarian sciences of Ukraine - Tretіak, A.; Dorosh, Y.; Tretіak, V.; Dyumina, K. (Land Management, Cadastre and Land Monitoring, 2018)
The article examines the issue of spatial organization and interactions, the influence of processes of spatial development of scientific and research land use in the system of National Academy of Agrarian Sciences of Ukraine (NAASU).In particular, the study of the development of economic thought suggests that most scholars - representatives of classical economic schools, in studying the problems of the development of the national economy are based, primarily on the time component, without paying due attention to the spatial aspects.It is substantiated that through generalization of the starting positions of numerous scientific theories the theoretical substantiation of the integrated system of management of spatial development of land use of institutions and enterprises of the National Academy of Agrarian Sciences of Ukraine and the increase of the efficiency of its functioning as a whole will be possible and will increase the efficiency of agrarian research. The above and causes the need for their study of systematization and adaptation to the present conditions. Insufficient consideration of spatial (territorial) features of the development of scientific research land use significantly reduces the practical value of the recommendations of scientists of NAASU.A.M.Tretyak [4, c. 285-286], introducing the concept of "territorial land management" as a spatial land management organization of the territory, states that it covers various branches of the economy, different types of organization, enterprises, institutions: agricultural, industrial, transport, etc. From his point of view, a characteristic feature of the territorial land management is as the "territorial land management" is carried out simultaneously in the territory of councils or groups of land ownership and land use, and sometimes in the territory of entire administrative districts. Accordingly, spatial organization includes a complex of processes of purposeful economic activity of business entities, including research and development in the agrarian sector, in a certain territory.At present, the process of theoretical and methodological reflection of a scientific system that describes the spatial organization and interactions, the impact of the processes of spatial development of research and development land use in the system of NAASU, taking into account macro- and microeconomic dynamics, is at an initial stage and needs further study.After all, spatial development of multidimensional ecological and economic systems in modern conditions requires a new methodological substantiation of approaches to synergetic study of the economy of scientific researches as the interaction of microeconomic agents, regional, national and global interactions, including the study of various spatial forms of organization of land use of scientific institutions and enterprises as centers of coordination and accumulation of ecological, economical and social interrelations between separate economic subjects, territorial we communities or regions.It is substantiated that the territorial and internal organization of the use and protection of the lands of scientific institutions and enterprises has a relation to spatial land use of the formation. In particular, it is the establishment of a differentiated regime for the use, protection and reproduction of land (soil) and other natural resources in accordance with the functional zoning of research and development land use, in particular the allocation of such zones [10, 11]:¨                area of scientific research fields - intended for basic research in the field of agriculture, including on irrigated and drained lands, plant growing, horticulture, viticulture, protection of soils and restoration of the most valuable properties of the earth and natural complexes, the regime of which is determined in accordance with the requirements established by the Regulation on research fields, approved by the Presidium of the NAAS, on the submission of academic councils of scientific- research institutions;¨                the growing area ofelite seeds and planting material of agricultural crops - is intended for placement of breeding and seed crop rotation of growing areas of new varieties of fruit and berries, grapes and hops, taking into account the conditions of cultivation of original and elite seeds, observance of technologies and varieties of agricultural machinery, the regime of which is determined by the land management project in relation to organization of the territory;¨                Regulated use zone - intended for placement of special forage crop rotation with the production of feed for the needs of breeding stock, experimental research on irrigated and drained lands, promotion of scientific developments, testing of new technology and technologies, the regime of which is determined by the land management project regarding the organization of the territory;¨                the zone of preservation of agro-environmental, nature protection and historical and cultural complexes and objects valuable for the agrarian science, the regime of which is determined by the legislation of Ukraine and the Presidium of the National Academy of Sciences of Ukraine;¨                Business zone - within its boundaries, economic activity is conducted, aimed at fulfilling tasks entrusted to a scientific institution, including research facilities and enterprises.It is substantiated that in the NAASU system, the effectiveness of the spatial economics of scientific and research land use is due to the zonal, territorial and intrapeculiarities of its organization.Keywords: spatial planning, scientific and research, territorial land management.